2004
DOI: 10.3928/1081-597x-20040301-11
|View full text |Cite
|
Sign up to set email alerts
|

Lamellar Crescentic Resection for Pellucid Marginal Corneal Degeneration

Abstract: PURPOSE: To evaluate the results of lamellar crescentic resection in pellucid marginal corneal degeneration. METHODS: Patients with pellucid marginal corneal degeneration who underwent lamellar crescentic resection from 1995 to 2000 at Labbafinejad Medical Center were assessed. Diagnosis was based on clinical findings of slit-lamp microscopy and confirmed by corneal topography and pachymetry. RESULTS: Fifteen eyes of nine patients (six male and three female) were operated. Mean patient age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Crescentic lamellar wedge resection is similar to full-thickness crescentic wedge resection, but only the abnormally thinned stroma is removed, followed by re-approximation of the residual, normal-thickness stromal edges ( Figure 5). 83,84 Like full-thickness crescentic wedge resection, crescentic lamellar wedge resection does not require donor tissue. The main advantage of crescentic lamellar wedge resection over full-thickness crescentic wedge resection is the maintenance of a closed globe.…”
Section: Full-thickness Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crescentic lamellar wedge resection is similar to full-thickness crescentic wedge resection, but only the abnormally thinned stroma is removed, followed by re-approximation of the residual, normal-thickness stromal edges ( Figure 5). 83,84 Like full-thickness crescentic wedge resection, crescentic lamellar wedge resection does not require donor tissue. The main advantage of crescentic lamellar wedge resection over full-thickness crescentic wedge resection is the maintenance of a closed globe.…”
Section: Full-thickness Interventionsmentioning
confidence: 99%
“…85 Several small studies have confirmed the efficacy of crescentic lamellar wedge resection in PMD ( Table 2). [83][84][85] Recently, Maccheron and Daya performed corneal wedge resection with partial or total lamellar dissection with the aim of improving corneal symmetry and optical clarity by shortening the vertical circumference of the cornea in eyes with combined PMD/keratoconus or keratoglobus. 85 The result was a statistically significant improvement in visual acuity with reduced astigmatism, although follow-up duration and outcomes varied among study participants.…”
Section: Full-thickness Interventionsmentioning
confidence: 99%
“…The management of PMD includes various modalities of treatment, including spectacles, rigid gas-permeable contact lenses [ 6 ]. Surgical management includes intracorneal ring segments [ 7 ], full-thickness crescentic wedge resection [ 8 ], lamellar crescentic wedge resection [ 9 ], deep anterior lamellar keratoplasty [ 10 ], and penetrating keratoplasty (PK) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%